Trends, tensions, and futures of maker education research: a 2025 vision for STEM+ disciplinary and transdisciplinary spaces for learning through making - Ioannou, Andri; Gravel, Brian E. (My University, 2024)
This special issue aims to sketch the present state of maker learning research, reveal possible tensions, and present future possibilities to articulate principles for learning through design in the era of maker education. The special issue was announced in 2022 in ETR&D, a leading academic journal in educational technology. Of the 50 submissions to the special issue, eighteen (18) were accepted for publication. The editors favored a robust inclusion of papers to help define the contours of the field at present. Four clusters of topics are identified in this collection of papers: (i) STEM+ disciplinary and transdisciplinary learning spaces; (ii) Digital technologies in making, opportunities and challenges; (iii) Assessment practices and frameworks; (iv) Representation, inclusion, and tensions around maker-centered initiatives and reforms. The editors of the special issue believe that these clusters reflect the current state-of-the-art in the field as well as significant questions to guide near future research. Reflecting on these papers but also the overall editorial process, the editors identified several opportunities and provide suggestions on how the field might expand moving forward.
Keywords: Learning through design; STEM+ · Educational technology; Maker education; Makerspaces